Labor force participation and the discouraged worker effect - John K. Dagsvik; Tom Kornstad; Terje Skjerpen (Statistics Norway, Research Department, 2010)
This paper analyzes labor force participation with particular reference to the discouraged worker effect. Discouraged workers are those who do not search for work because they view their chances of finding a suitable job as too low. The theoretical point of departure is a search model where the worker evaluates the expected utility of searching for work and decides to participate in the labor market if the expected utility of the search exceeds the utility of not working. From this framework we derive an empirical model for the probability that the worker will be unemployed or employed as a function of the probability of getting an acceptable job, given that the worker searches for work. The model is estimated on a sample of married and cohabitating women in Norway covering the period from 1988 to 2008. The results show that the discouraged worker effect is substantial. On average, about one third of those who are out of the labor force are discouraged according to our analysis.
Keywords: J21; J22; J64; 330; Discouraged workers; Labor force participation; Random utility modeling